Coping with burnout? Measuring the links between workplace conflicts, work-related stress, and burnout - Danauskė, Evelina; Raišienė, Agota Giedrė; Korsakienė, Renata (Business: Theory and Practice, 2023)
Purpose. The aim of the paper is to investigate the relationship between workplace conflicts and employee burnout. Design/methodology/approach. The survey method was chosen, and the questionnaire was posted online to share among Lithuanian employees. Finally, 495 employees completed the questionnaire, which included four parts: questions about workplace conflicts, burnout, burnout due to conflicts, and consequences of burnout. Statistical analysis was used to process the research data. Findings. The study revealed that the more conflicts employees have with clients, colleagues, or managers, the more burnout they experience as a consequence. Furthermore, conflicts with colleagues have the strongest relationship with consequences of burnout which are not as unambiguous as they may also be the outcome of burnout. Research limitations/implications. The study was conducted in Lithuania and revealed the conflict-induced burnout of employees and the consequences of the burnout they face. Practical implications. Understanding the links between conflict at work and burnout let organizational leaders prioritize conflict resolution, pay more attention to the mental health of employees, and protect the organization from the costly consequences of burnout. Originality/Value. This study reveals the consequences of labour conflicts not only in the context of burnout but also in its consequences which allow to understand the real threat of disputes.